2011
DOI: 10.1186/1756-0500-4-390
|View full text |Cite
|
Sign up to set email alerts
|

Strengthening organizational performance through accreditation research-a framework for twelve interrelated studies: the ACCREDIT project study protocol

Abstract: BackgroundService accreditation is a structured process of recognising and promoting performance and adherence to standards. Typically, accreditation agencies either receive standards from an authorized body or develop new and upgrade existing standards through research and expert views. They then apply standards, criteria and performance indicators, testing their effects, and monitoring compliance with them. The accreditation process has been widely adopted. The international investments in accreditation are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
43
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(45 citation statements)
references
References 27 publications
1
43
0
1
Order By: Relevance
“…In this study, perceptions of the respondents that drivers of organizational changes-in almost equal percentage are management and the expert team, shows that not in all institutions management is perceived as overtaking the role to implement changes and the team does not perceive them as leaders toward positive changes. However, in practice, positive changes are certainly driven by the management (Braithwaite et al, 2011). The level to which employees can participate in the planning and implementing of such processes is in the power of the management (Pahkin et al, 2014), having in mind that changes to be successful employees need to be involved as much as possible (Braithwaite et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, perceptions of the respondents that drivers of organizational changes-in almost equal percentage are management and the expert team, shows that not in all institutions management is perceived as overtaking the role to implement changes and the team does not perceive them as leaders toward positive changes. However, in practice, positive changes are certainly driven by the management (Braithwaite et al, 2011). The level to which employees can participate in the planning and implementing of such processes is in the power of the management (Pahkin et al, 2014), having in mind that changes to be successful employees need to be involved as much as possible (Braithwaite et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, in order to obtain the accreditation, organisations are assessed against externally designed standards. The standards are intended to cover all aspects of healthcare provision by investigating the organisation in terms of management and clinical performance (Braithwaite et al, 2011;Greenfield and Braithwaite, 2008;Pomey et al, 2010;Shaw, 2004b). Many of these standards are often defined in the language of control; for example as output standards, input standards and process standards that are used to measure the performance of the organisation (Montagu, 2003;Neely et al, 2001;Brown, 1996).…”
Section: Accreditation As a Regulatory Control Systemmentioning
confidence: 99%
“…Whether they actually do, is debatable and a number of studies have indicated the problematic nature of achieving these goals (Scrivens, 1997a;de Walcque et al, 2008). The standards are applied against current organisational activities typically by way of self-assessment (such as filling out questionnaires), desk appraisal of internal documents and on-site visits, usually by peers (Montagu, 2003;Braithwaite et al, 2011).…”
Section: The Nature Of Accreditation Systemsmentioning
confidence: 99%
“…This information is vital for both employee and the hospital and aids in the assurance that the hospital is staffed appropriately. [30,[38][39][40][41][42] Apart from being essential items in hospital management, proper personnel files are also essential for hospital accreditation. [43][44][45] Rwanda's Ministry of Health, which aims to strengthen health systems by ensuring provision of high quality services, adopted a hospital accreditation system in 2006 as one of the main strategies to improve quality of care.…”
Section: Introductionmentioning
confidence: 99%